A new automatic AHP tool to assess the forest vulnerability to wind damage - Kašpar, Jan; Badr, Sanaa; Tahri, Meryem; Maanan, Mohamed; Tahri, Haytham; Mohammadi, Zohreh; Novotný, Miroslav; Yousfi, Noura (Ecological indicators, 2025)
This study performs an analytical hierarchy process (AHP) approach in conjunction with spatial data to map the vulnerability of forests to wind damage. Forest management can be crucial in enhancing the resilience of forests to wind disturbances. However, to support decision-making processes to effectively manage forests, it is relevant to determine the most influential forest tree destruction drivers and calculate their weights. The criteria considered are wind speed, wind direction, the proportion of Norway spruce Picea abies, edaphic factors and tree age in the stand. However, a major obstacle to the application of decision-making aid is the inconsistency of the judgment of experts, thus the judgment matrices need to be adjusted. Here, An efficient readjusting AHP technique (Re-AHP) was developed to improve the consistency ratio. To do this, the pairwise comparison matrix in AHP method had to be adjusted to address the issue of inconsistent ratios, while retaining the original judgment intention. A user-friendly Re-AHP Matlab App Designer was designed to readjust the comparison matrix for each expert, using the case of susceptibility to wind damage as an illustration. The wind damage vulnerability map showed that over 80% of the area is at medium and high vulnerability levels. The validation proved that the selected method is the most efficient. The new tool was used to develop a speedy method for the forest context. While the study focused on a specific site, the developed methodology is universally applicable and can be adapted to various forest sites worldwide. •New user-friendly re-adjust analytic hierarchy process (Re-AHP) MATLAB App Designer.•Automatic AHP pairwise matrix reconstruction method is suitable for various users.•Mapping potential prone sites to wind damage.